Unearthing phytochemicals as natural inhibitors for pantothenate synthetase in Mycobacterium tuberculosis: A computational approach - Chouhan, Mandeep; Tiwari, Prashant Kumar; Mishra, Richa; Gupta, Saurabh; Kumar, Mukesh; Almuqri, Eman Abdullah; Ibrahim, Nasir A.; Basher, Nosiba Suliman; Chaudhary, Anis Ahmad; Dwivedi, Vivek Dhar; Verma, Devvret; Kumar, Sanjay (Frontiers in Pharmacology, 2024)
Pantothenate synthetase protein plays a pivotal role in the biosynthesis of coenzyme A (CoA), a crucial molecule involved in a number of cellular processes including metabolism of fatty acid, energy production, and the synthesis of various biomolecules, which is neccessary for the survival of Mycobacterium tuberculosis (Mtb). Therefore, inhibiting this protein, could disrupt CoA synthesis, leading to the impairment of vital metabolic processes within the bacterium, ultimately inhibiting its growth and survival. This study employed molecular docking, structure based virtual screening, and MD simulation to identify promising phytochemical compounds targeting pantothenate synthetase for tuberculosis treatment. Among 239 compounds, the top three (Rutin, Sesamin and Catechin gallate) were selected with binding energy values ranging from -11 to -10.3 kcal/mol, and the selected complexes showed RMSD (<3 Å) for 100ns MD simulation time. Furthermore, MM/GBSA binding free energy calculations affirmed the stability of these three selected phytochemicals with a binding energy ranges from -82.24±9.35 to -66.83±4.5 kcal/mol. Hence, these identified natural plant derived compound as potential inhibitor of pantothenate synthetase, could be utilized to inhibit tuberculosis infection in human.